Are Migrant Workers in DKI Jakarta More Welfare than Non Migrants?: A Data Analysis of National Social and Economic Survey (Susenas) 2013 - Chotib,; Nurbaiti, Beti (UI Scholars Hub, 2018)
The objective of this research is assessing welfare status of Worker in DKI Jakarta and its relationships to migration status and other determinant variables (other socio-demographic variables). By using Susenas (National Socio-Economics Survey) 2013 raw data as a source of research data, this research conducted analysis with two stages: 1) Constructing the worker’s welfare status by using PCA (Principle Component Analysis); 2) Statistical analysis to show the effect of migration status and other variables on worker’s welfare status in DKI Jakarta. The statistical analysis employed both descriptive and inferential statistics. The result of descriptive analysis shows that the welfare workers tend to be in those with some characteristics as follow: non-migrant status, older age, female, higher education, unmarried workers, and workers with formal job status. The inferential analysis using binary logistic regression exhibits that migration status and other socio-demographic variables have significant effects on welfare status of workers.